Obadiah Stevens journal - Stevens, Obadiah
Journal kept by Stevens as an American prisoner of war in a British prison on the island of Malta during the War of 1812. Includes typewritten transcript of journal.
Typewritten transcript, in part.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Prisons -- Malta; United States -- History -- War of 1812 -- Prisoners and prisons, British